Business Strategy In Realizing Prosperity Of Owners And Employees Based On Value Chain Analysis - Firdaus (Institut Agama Islam Negeri Metro), Wihda Yanuar (Universitas Muhammadiyah Lampung, 2024)
There are three problem formulations in this research, namely: (1) What is the business strategy for Bakso Lahar; (2) What is the maslahah-based value chain strategy for Bakso Lahar; (3). What is a maslahah-based value chain strategy in realizing the welfare of owners and employees at Bakso Lahar. This type of research is qualitative with a phenomenological and normative approach. Primary data in this research was obtained from business owners, financial managers, marketing, production, employees and consumers. Secondary data is in the form of books, journals or documentation related to Bakso Lahar. Data collection methods through observation, interviews and documentation. The data validity testing uses triangulation and transferability. The research results show that: (1) The Bakso Lahar business strategy implemented in terms of business capital uses the syirkah system, Islamic work culture, providing the best service to consumers and using digital marketing strategies. (2) Bakso Lahar maslahah-based value chain strategy, namely differentiation in the form of tayib and halal principles and focus on Muslim families. (3) The welfare felt by business owners and employees from maslahah-based value chain activities produces benefits in the form of profits and blessings from an economic, social and spiritual perspective. The implications of this research finding include two things, namely theoretical implications and practical implications. (1) The theoretical implications of the Bakso Lahar value chain are in accordance with the principle of benefit, but it would be even better if we continued to optimize other value chains as part of the business strategy, not only on differentiation and focus but also on efforts to achieve cost leadership so that all consumers can feel the benefits in the form of cheap product prices. (2) Practical implications, the owner of Bakso Lahar should make more efforts to improve employee performance by providing training that can improve skills and also giving clear status to employees as contract or permanent employees so that employees become more loyal to the company.